Androgen Effects on the Adrenergic System of the Vascular, Airway, and Cardiac Myocytes and Their Relevance in Pathological Processes - Abril Carbajal-García; Jorge Reyes-García; Luis M. Montaño (International Journal of Endocrinology)
Introduction. Androgen signaling comprises nongenomic and genomic pathways. Nongenomic actions are not related to the binding of the androgen receptor (AR) and occur rapidly. The genomic effects implicate the binding to a cytosolic AR, leading to protein synthesis. Both events are independent of each other. Genomic effects have been associated with different pathologies such as vascular ischemia, hypertension, asthma, and cardiovascular diseases. Catecholamines play a crucial role in regulating vascular smooth muscle (VSM), airway smooth muscle (ASM), and cardiac muscle (CM) function and tone. Objective. The aim of this review is an updated analysis of the role of androgens in the adrenergic system of vascular, airway, and cardiac myocytes. Body. Testosterone (T) favors vasoconstriction, and its concentration fluctuation during life stages can affect the vascular tone and might contribute to the development of hypertension. In the VSM, T increases α1-adrenergic receptors (α1-ARs) and decreases adenylyl cyclase expression, favoring high blood pressure and hypertension. Androgens have also been associated with asthma. During puberty, girls are more susceptible to present asthma symptoms than boys because of the increment in the plasmatic concentrations of T in young men. In the ASM, β2-ARs are responsible for the bronchodilator effect, and T augments the expression of β2-ARs evoking an increase in the relaxing response to salbutamol. The levels of T are also associated with an increment in atherosclerosis and cardiovascular risk. In the CM, activation of α1A-ARs and β2-ARs increases the ionotropic activity, leading to the development of contraction, and T upregulates the expression of both receptors and improves the myocardial performance. Conclusions. Androgens play an essential role in the adrenergic system of vascular, airway, and cardiac myocytes, favoring either a state of health or disease. While the use of androgens as a therapeutic tool for treating asthma symptoms or heart disease is proposed, the vascular system is warmly affected.